Rethinking Combative Dialogue: Comparative Philosophy as a Resource for Examining Models of Dialogue - Mattice, Sarah A. (Paideusis)

(untitled) (Canadian Philosophy of Education Society, 2010)
In this essay I am concerned with our understanding of philosophical dialogue. I will examine the most prevalent western model of dialogue—the combat model—and suggest some flaws in this model. I will outline concerns as to how standards for what counts as ‘philosophical’ are determined, and use this outline to frame preliminary objections to conceiving of philosophical dialogue as combative. Noting that philosophy is a socially and historically rooted practice, I argue that the view of philosophy as a kind of combat has its origins in features of ancient Greek life. Next, I will look to other cultures and traditions for differing conceptual resources. Specifically, I look to ancient China’s philosophical narrative as one that does not primarily conceive of philosophy in terms of combat. I conclude by suggesting the relevance of this inquiry into methodology for practices of teaching philosophy.